## Monday, March 11, 2019

### Solution To Laplace Transform Differential Equation

The problem again:

Use Laplace transforms to solve the differential equation:

d 3 Y/ dt 3 -    d Y /dt   =   0

Using the conditions:  Y(0) =  1,  Y’(0) =  0  and  Y" (0) = 1

Solution:  We Write:

£ { d 3 Y/ dt 3  } =  3   y(s)  -   Y(0) 2    -    Y'(0) s  -  Y"(0)

=    3  y(s)  -   2    -   1

£ {dY / dt}   =    s y(s)   -  Y(0)  - Y"(0)

=    s y(s) -  1

Substitute the expression for each transform:

3  y(s)  -   2    - 1   =   0

Collect like terms and transpose:

(3  -     s)  y(s)   =      2    +  1

Solve for y(s):

y(s)   =   ( 2    +  1  ) /  (3  -     s)  =    ( 2    +  1  ) /  s (  2    -  1   )

Use  of partial fractions yields:

A/ s   +    B/ (  2    -  1   )     =   2    +  1

Then:

A (  2    -  1   )   +  Bs   =   2    +  1

Whence:

A 2     -  A    +  B s    =   2   +   1

Yielding values (by equating coefficients):

A    = 1

B   -     A   =  0

So:  B  =    1

è

( 2    +  1  ) /  s (  2    -  1   )  =

1 / s     +   1 /  ( 2    -  1   )

We then need to take the inverse Laplace transform :

£ -1  [1 / s     +   1 /  ( 2    -  1   ) ]

=

£ -1  [1 / s ]    + £ -1 [ 1 /  ( 2    -  1   )]

From a table of transforms (see bottom of previous post from  March 2nd):

We see:   1/s   is inverse transformed to  1

And similarly:  1 /  ( 2    -  1   )]  ->   cosh (t)

Then the solution to the DE is:  Y (t)   =   1   +    cosh (t)

Check soln.  to  Y/ dt 3 -    d Y /dt   =   0 :

(1+ cosh (t))/ dt 3   =   0

d  (1   +    cosh (t))/dt   =   0

Then:   0   -  0  =  0

So:

Y/ dt 3 -    d Y /dt   =   0